The presence and severity of nonalcoholic steatohepatitis is associated with specific changes in circulating bile acids. Issue 2 (23rd December 2017) - Puri, Puneet; Daita, Kalyani; Joyce, Andrew; Mirshahi, Faridoddin; Santhekadur, Prasanna K.; Cazanave, Sophie; Luketic, Velimir A; Siddiqui, Mohammad S.; Boyett, Sherry; Min, Hae‐Ki; Kumar, Divya P.; Kohli, Rohit; et al.
Abstract : The histologic spectrum of nonalcoholic fatty liver disease (NAFLD) includes fatty liver (NAFL) and steatohepatitis (NASH), which can progress to cirrhosis in up to 20% of NASH patients. Bile acids (BA) are linked to the pathogenesis and therapy of NASH. We (1) characterized the plasma BA profile in biopsy‐proven NAFL and NASH and compared to controls and (2) related the plasma BA profile to liver histologic features, disease activity, and fibrosis. Liquid chromatography/mass spectrometry quantified BAs. Descriptive statistics, paired and multiple group comparisons, and regression analyses were performed. Of 86 patients (24 controls, 25 NAFL, and 37 NASH; mean age 51.8 years and body mass index 31.9 kg/m 2 ), 66% were women. Increased total primary BAs and decreased secondary BAs (both P  < 0.05) characterized NASH. Total conjugated primary BAs were significantly higher in NASH versus NAFL ( P  = 0.047) and versus controls ( P  < 0.0001). NASH had higher conjugated to unconjugated chenodeoxycholate ( P  = 0.04), cholate ( P  = 0.0004), and total primary BAs ( P  < 0.0001). The total cholate to chenodeoxycholate ratio was significantly higher in NAFLD without ( P  = 0.005) and with ( P  = 0.02) diabetes. Increased key BAs were associated with higher grades of steatosis (taurocholate), lobular (glycocholate) and portal inflammation (taurolithocholate), and hepatocyte ballooning (taurocholate). Conjugated cholate and taurocholate directly and secondary to primary BA ratio inversely correlated to NAFLD activity score. A higher ratio of total secondary to primary BA decreased (odds ratio, 0.57; P  = 0.004) and higher conjugated cholate increased the likelihood of significant fibrosis (F≥2) ( P  = 0.007). Conclusion : NAFLD is associated with significantly altered circulating BA composition, likely unaffected by type 2 diabetes, and correlated with histological features of NASH; these observations provide the foundation for future hypothesis‐driven studies of specific effects of BAs on specific aspects of NASH. (Hepatology 2018;67:534‐548).